Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1101/762492
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neuro-transcriptomic signatures for mood disorder morbidity and suicide mortality

Abstract: Suicidal behaviors are strongly linked with mood disorders, but the specific neurobiological and functional gene-expression correlates for this linkage remain elusive. We therefore tested the hypothesis that a convergent neuroanatomical and gene-expression signature will underlie mood disorder associated psychiatric morbidity and related suicide mortality. To do so, first, we applied an anatomical likelihood estimation (ALE) MRI meta-analysis across 72 voxel-based morphometry (VBM) studies including 2387 (livi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…JASPAR 2018 TFs binding profiling: Given the role of transcription factors (TFs) in regulating gene expression via specific DNA-binding domains (motifs) in the gene promoters, we followedup on our previous study (Jabbi et al 2020) that identified whole transcriptome gene expression profiles in mood disorders, with the aim to explore in more detail, mood disorder transcriptomics by identifying TF motifs. To this goal, we used JASPAR TF binding database to identify motifs that were associated with DEGs in BD vs. controls; MDD vs. controls, and in pooled mood disorder individuals with high vs. low Axis-I comorbidity.…”
Section: Differential Gene Expression Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…JASPAR 2018 TFs binding profiling: Given the role of transcription factors (TFs) in regulating gene expression via specific DNA-binding domains (motifs) in the gene promoters, we followedup on our previous study (Jabbi et al 2020) that identified whole transcriptome gene expression profiles in mood disorders, with the aim to explore in more detail, mood disorder transcriptomics by identifying TF motifs. To this goal, we used JASPAR TF binding database to identify motifs that were associated with DEGs in BD vs. controls; MDD vs. controls, and in pooled mood disorder individuals with high vs. low Axis-I comorbidity.…”
Section: Differential Gene Expression Analysismentioning
confidence: 99%
“…Using the anatomical likelihood estimation meta-analysis (Eickhoff et al 2009), we previously identified the right anterior insula as the brain region with the most extensive GMV reduction in mood disorders relative to healthy controls ( Figure. 1A) (Jabbi et al 2020). We manually reconstructed this region in ITKSnap (http://www.itksnap.org/pmwiki/pmwiki.php) and provided this 3-D volume information to the pathologist at the brain bank to guide postmortem dissection of anterior insula tissue from each sample for subsequent RNA extraction and RNA-sequencing.…”
Section: Robust Imaging-guided Transcriptomicsmentioning
confidence: 99%
See 2 more Smart Citations
“…71 Pursuant to Article 7(2), that right of residence shall extend to third country national family members accompanying or joining the EEA national in the host State. 72 Referring to its Gunnarsson judgment, 73 the Court held that the home EEA State may not deter its nationals from moving to another EEA State in the exercise of the freedom of movement under EEA law. 74 The Court held that a right to move freely from the home EEA State to another EEA State cannot be fully achieved if the EEA national may be deterred from exercising the freedom by obstacles raised by the home State to the right of residence of a spouse.…”
Section: The Normative Impact Of the Eu Charter For Eea Fundamental Rmentioning
confidence: 99%